Structual and biochemical characterisation of the endoplasmic reticulum alpha-glucosidases - Caputo, A (2015)
ER alpha-glucosidases I and II are glycosyl hydrolases that play a key role in eukaryotic glycoprotein folding quality control. Removal of two glucose residues from the N-glycan attached to a protein allows association with calnexin or calreticulin which enable folding through associated accessory proteins. Many enveloped viruses utilise the calnexin cycle for the correct folding of their surface glycoproteins. Inhibition of the ER alpha-glucosidases causes misfolding of these viral glycoproteins and reduction of virion secretion and/or infectivity. Thus, inhibition of these glucosidases is a potential broad-spectrum antiviral strategy with clinical relevance. Inhibition by certain iminosugars, a class of glycomimetics, has given rise to a clinical candidate against dengue virus. To date there are no high-resolution structures available for either of the mammalian ER alpha-glucosidases. Presented in this thesis is the work toward the structural and biochemical characterisation of both alpha-glucosidases. Large-scale production of both murine glucosidases is described along with biochemical characterisation against a number of substrates. Glucosidase I is a challenging target for biochemical and structural studies. Described is the purification and confirmation of enzymatic activity. Biophysical techniques show that it is well folded and able to bind to iminosugars. Preliminary attempts at crystallisation have resulted in poorly diffracting crystals to 5 Å. This work enables future optimisation toward an atomic resolution structure of glucosidase I. Glucosidase II plays a complex role in the kinetics of glycoprotein processing in the calnexin cycle. Production of the heterodimeric enzyme has enabled a detailed biochemical characterisation with a range of substrates and inhibitors. Structural characterisation of a large fragment of glucosidase II has enabled new insights into the details of heterodimerisation, substrate specificity, and the basis of iminosugar inhibition. This information can guide future development of more selective inhibitors.